Investigating the Factors Affecting Mental Health of Public School Teachers in Afghanistan: A Case Study of Andkhoy District - Faridoon Qayobi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to investigate the mental health status of public school teachers in Andkhoy District, Faryab Province, Afghanistan, and to identify the factors influencing their psychological well-being. Using a quantitative survey design, data were collected from 210 teachers selected through stratified proportional random sampling. The GHQ-28 questionnaire was employed to measure four dimensions of mental health: physical symptoms, anxiety and insomnia, social dysfunction, and depression. Data analysis was conducted using descriptive and inferential statistics with SPSS version 26. The findings reveal that teachers’ overall mental health is at a moderate or borderline level, indicating the presence of considerable psychological stress. Among the dimensions, depression shows the highest mean score, suggesting a greater vulnerability to emotional distress. However, inferential analysis indicates that demographic variables such as gender, marital status, and teaching experience do not have a significant effect on mental health. This suggests that environmental and occupational factors, including workload, limited resources, and lack of institutional support, play a more dominant role in shaping teachers’ psychological conditions. The study highlights the urgent need for targeted interventions, such as counseling services, stress management programs, and improved organizational support. Enhancing teachers’ mental health is essential not only for their well-being but also for improving teaching quality and educational outcomes.